2015
DOI: 10.1080/14680629.2014.1000943
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of stiffness, low-temperature cracking, rutting, moisture damage, and fatigue performance of WMA mixes

Abstract: Despite the environmental and compaction benefits of warm mix asphalt (WMA), several researchers have expressed concerns over laboratory and field performances of WMA mixes. In this study, a wide range of laboratory tests, namely, dynamic modulus, creep compliance, fatigue, moisture damage, and rutting, was conducted to evaluate the performance of different types of WMA mixes. For this purpose, three WMA mixes, consisting of one mix produced using a zeolite-based WMA additive (containing water), one surface co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In case of fatigue resistance, results of two laboratory studies showed that although the chemical additives and foamed mixtures have a lower fatigue resistance compared to conventional HMA [48], Sasobit as a wax additive can improve fatigue performance especially when the modified asphalt mixtures are compacted at lower temperature (100-115 • C) [49,50]. Additionally, the laboratory evaluation of fatigue life for foamed WMA mixtures using four-point beam fatigue tests exhibited higher fatigue life compared to HMA mixtures [51].…”
Section: Evaluation Type Referencesmentioning
confidence: 99%
“…In case of fatigue resistance, results of two laboratory studies showed that although the chemical additives and foamed mixtures have a lower fatigue resistance compared to conventional HMA [48], Sasobit as a wax additive can improve fatigue performance especially when the modified asphalt mixtures are compacted at lower temperature (100-115 • C) [49,50]. Additionally, the laboratory evaluation of fatigue life for foamed WMA mixtures using four-point beam fatigue tests exhibited higher fatigue life compared to HMA mixtures [51].…”
Section: Evaluation Type Referencesmentioning
confidence: 99%
“…HMAC in the study had higher complex modulus at all the evaluated temperatures and viscosity was also higher [5]. Laboratory tests, including dynamic modulus, creep compliance, fatigue, moisture damage, and rutting, were conducted to evaluate the performance of different types of WMA mixes [6]. Han chose two kinds of aggregates (basalt and limestone) with obvious differences to study the impact of aggregates on the high modulus mixture properties of hard asphalt (such as high temperature properties, modulus, and fatigue resistance), 2 Advances in Materials Science and Engineering showing that a balanced design of high temperature performance, modulus, and fatigue resistance properties can be achieved on the mixture thronging the gradation and the hard asphalt dosage adjustment, for different properties aggregate [7].…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, moisture damage can significantly shorten the repair cycles and the lifetime of asphalt highway, accordingly increasing the cost of maintenance and repair [13,14]. Therefore, it is necessary to study the interfacial adhesive properties between the acidic aggregate and the asphalt [15], due to the important economic and social significances [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are not able to improve the interfacial bonding strength between acidic aggregates and asphalt after mixing and construction. Once the water enters the asphalt concrete, hydrogen bonding can take place on the hydrophilic surface of the aggregates, displacing asphalt from the aggregate and causing stripping of the asphalt membrane [16,25]. In actual fact, mineral aggregates are often partly composed of a mixture of neutral and acidic aggregates, and it is necessary to develop new technologies or ASA materials in order to enhance the interfacial adhesive property between acidic aggregates and asphalt.…”
Section: Introductionmentioning
confidence: 99%